Incidence, treatment and recurrence of endometriosis in a UK-based population analysis using data from The Health Improvement Network and the Hospital Episode Statistics database. (3rd September 2017) - Cea Soriano, Lucia; López-Garcia, Esther; Schulze-Rath, Renate; Garcia Rodríguez, Luis A.
Abstract: Purpose: This retrospective study used medical records from The Health Improvement Network (THIN) and Hospital Episode Statistics (HES) database to evaluate endometriosis (incidence, treatment and need for recurrent invasive procedures) in the general UK population. Materials and methods: Women aged 12–54 years between January 2000 and December 2010, with a Read code for endometriosis, were identified in THIN. Cases were validated by manual review of free-text comments in medical records and responses to physician questionnaires. False-negative cases were identified among women with Read codes for hysterectomy or dysmenorrhea. Prescriptions of medical therapies for endometriosis were identified in THIN. Cases of single and recurrent invasive procedures were identified in women with medical records in both THIN and HES. Results: Overall, 5087 women had a Read code for endometriosis, corresponding to an incidence of 1.02 (95% confidence interval [CI]: 0.99–1.05) per 1000 person-years. After case validation, the estimate was 1.46 (95% CI: 1.43–1.50) per 1000 person-years. Medical therapy was prescribed to 55.5% of women with endometriosis in the first year after diagnosis. In total, 48.3% of women received invasive treatment during the study period; approximately one-fifth of these women required further invasive treatment, mainly in the 3 years after the index procedure. Conclusions: Using Read codes as the only method to identify women with endometriosis underestimates incidence. Over half of women with recorded endometriosis are prescribed medical therapy in the first year after diagnosis. Women with diagnosed endometriosis are at risk of requiring recurrent invasive procedures.